GWAS of mosaic loss of chromosome Y highlights genetic effects on blood cell differentiation - Chikashi Terao (Nature Portfolio, 2019)
Mosaic loss of chromosome Y (mLOY) is associated with age and smoking but also genetic factors play a role. Here, Terao et al. perform GWAS for mLOY in 95,380 Japanese men and identify 46 loci that overlap with hematopoietic stem cell enhancers and transcription factor binding sites critical for hematopoiesis.